Luxury Expenses of Shadow Education: A Comparative Study of Iranian Students, Parents and Teachers' Views - Naser Shirbagi; Jafar Afshinfar; Rozhin Ghaslani; Sharareh Sadeghi; Shahab Nasirinia (Comparative Education Society of Iran ( CESIR), 2019)
The purpose of present research was investigating factors and attitudes affecting participation in private touring classes. A descriptive survey method with a quantitative approach was used. The participants were selected from three   groups: high school students, their teachers and parents. Using a stratified random sampling method, 900 individuals were selected as samples. Based on the findings of the study, English, math, and sciences   were the most used subjects for private supplementary tutoring. Research findings revealed that parents with higher incomes are more likely to send their children to private tutoring classes.   From the views of teachers and parents, the main goals of participating in private tutoring classes for students are to better understand the subjects and improve their performance in the exams and national tests. Most teachers and students acknowledged the effectiveness of private tutoring. Although parents and teachers noticed that a combination of factors contributed to the demand for private supplementary tutoring of students, their ratings were significantly different from what the students rated. Private tutoring, like helping the students with their homework, is one of the options parents may consider when they want to value and respond to the demands of their children for additional support and resources available within the family. Although Ministry of Education as the main administrator should monitor the activities of such centers, it does not appear to be very successful in practice.